The Routledge companion to religion and film - Lyden, John, 1959- (London ; New York : Routledge, 2009)
Going beyond overtly religious or religion-themed movies, this companion introduces analysis of religious influences to be found in a broad range of mainstream productions & deploys a range of methodologies, including psychoanalytical, theological, & feminist approaches & audience reception.
Introduction / John Lyden -- History of the interaction between religion and film : focus on Western Christianity -- Silent cinema and religion : an overview (1895-1930) / Terry Lindvall -- The era of censorship (1930-1967) / Andrew Quicke -- The Roman Catholic Church and cinema (1967 to the present) / Peter Malone -- Modern Protestant approaches to film (1960 to the present) / Bryan Stone -- Depictions of and by religious practitioners in films -- Judaism / Melanie Wright -- Christianity / Craig Detweiler -- Islam / Amir Hussain -- Hinduism / Rachel Dwyer -- Buddhism / Francisca Cho -- Postcolonial religious syncretism : focus on the Philippines, Peru, and Mexico / Antonio D. Sison -- Religion in Japanese film : focus on anime / Jolyon Baraka Thomas -- New religious movements / Paul Thomas -- Academic approaches to the study of religion and film -- Feminism / Gaye Williams Ortiz -- Audience reception / Clive Marsh -- Cultural theory and cultural studies / Gordon Lynch -- Psychoanalysis / Kent L. Brintnall -- Theological approaches / Robert K. Johnston -- Categories applicable to religion and film studies -- Narrative / Roy M. Anker -- Redemption / Christopher Deacy -- Apocalyptic / Conrad Ostwalt -- Heroes and superheroes / Robert Jewett and John Shelton Lawrence -- Horror and the demonic / Douglas E. Cowan -- Jesus and Christ-figures / Adele Reinhartz -- Iconography / Diane Apostolos-Cappadona -- Sacrifice / Jon Pahl -- Ethics / Jolyon Mitchell.
Includes bibliographical references and index.
Keywords: Motion pictures -- Religious aspects; Motion pictures -- Moral and ethical aspects; Religious films; Religion in motion pictures